2021
DOI: 10.3389/fphys.2021.720531
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the Effects of Foam Rolling and Stretching on Physical Performance. A Systematic Review and Meta-Analysis

Abstract: Foam rolling and stretching with its various techniques are frequently used as a warm-up routine to increase the range of motion of a joint. While the magnitude of the changes in range of motion between foam rolling and stretching (static and dynamic techniques) is similar, it is not clear if this also holds true for performance parameters (e.g., strength, jump height). The purpose of this meta-analysis was to compare the effects of an acute bout of foam rolling (with and without vibration) with an acute bout … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
30
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 50 publications
1
30
0
2
Order By: Relevance
“…In rehabilitation settings, FR is implemented within the strength training regime. Different FR tools are used, ranging from types of roller massage with varying densities, and to some extent, inclusion of motorized technology that creates vibration with FR [ 1 , 2 ]. Researchers recommend one to three sets of FR, with rolling durations of 30–120 s per set to attain the benefits of FR [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In rehabilitation settings, FR is implemented within the strength training regime. Different FR tools are used, ranging from types of roller massage with varying densities, and to some extent, inclusion of motorized technology that creates vibration with FR [ 1 , 2 ]. Researchers recommend one to three sets of FR, with rolling durations of 30–120 s per set to attain the benefits of FR [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, FR posted contrasting outcomes with regard to recovery [ 2 , 15 , 18 ]. Non-enhancement of performance with FR were also documented [ 1 , 2 , 15 , 18 ] [ While these reviews highlight the gaining popularity of FR in athletic, recreational, and rehabilitation settings, a majority of the reviews examined acute settings.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been reported that VFR can increase muscle strength and jump performance [2,3], although the changes in these variables were not significant [5,6]. The additional vibration stimulus of VFR is likely the reason why VFR has been found to be more effective in increasing the ROM of a joint [1] and preparing for performance tasks [2], compared to normal FR. The possible superior effect of VFR over FR alone could be attributed to the greater changes in mechanoreceptors, e.g., Pacinian corpuscles caused by vibration stimulation [7].…”
Section: Introductionmentioning
confidence: 94%
“…Vibration foam rolling (VFR) is a self-care technique involving the simultaneous use of foam rolling (FR) and vibration therapy, which shows the potential to have a favorable warm-up effect in increasing range of motion (ROM) [1] or performance [2] compared to conventional FR. In fact, recent studies have shown that VFR can increase range of motion (ROM) [1,3,4] and decrease muscle stiffness [3,5,6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation